2022
DOI: 10.1093/biolre/ioac029
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine C-X-C receptor 4 mediates recruitment of bone marrow-derived nonhematopoietic and immune cells to the pregnant uterus

Abstract: Bone marrow-derived progenitor cells (BMDPCs) are mobilized to the circulation in pregnancy and get recruited to the pregnant decidua where they contribute functionally to decidualization and successful implantation. However, the molecular mechanisms underlying BMDPCs recruitment to the decidua are unknown. CXCL12 ligand and its CXCR4 receptor play crucial roles in mobilization and homing of stem/progenitor cells to various tissues. To investigate the role of CXCL12-CXCR4 axis in BMDPCs recruitment to decidua,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Specifically, the proportions of NK cells, macrophages, and monocytes were significantly decreased, while granulocytes were significantly increased in decidua of CXCR4-KO mice. In agreement, we have previously shown that genetic ablation of CXCR4 in adult BM cells — including NK cells, monocytes, macrophages and granulocytes — affects their recruitment to the mouse implantation site ( 27 ). Moreover, the CXCL12/CXCR4 axis has been reported to be important for recruitment of NK cells ( 50 ) and DCs ( 51 ) to decidua.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, the proportions of NK cells, macrophages, and monocytes were significantly decreased, while granulocytes were significantly increased in decidua of CXCR4-KO mice. In agreement, we have previously shown that genetic ablation of CXCR4 in adult BM cells — including NK cells, monocytes, macrophages and granulocytes — affects their recruitment to the mouse implantation site ( 27 ). Moreover, the CXCL12/CXCR4 axis has been reported to be important for recruitment of NK cells ( 50 ) and DCs ( 51 ) to decidua.…”
Section: Discussionsupporting
confidence: 86%
“…Mice were maintained in a controlled environment at the Animal Facility of Yale School of Medicine with a 12-hour light, 12-hour dark cycle with ad libitum access to food and water. To generate TM-inducible CXCR4-KO mice, we used the Cre/LoxP TM-inducible system, as we described before ( 27 ). All mice were purchased from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, transformation of the cycling endometrium into the decidua of pregnancy depends critically on uterine chemokine signals, transvascular migration of circulating NK cells and BM-MSC, and their proliferative expansion and phenotypic differentiation into effective homeostatic regulators of the maternal-fetal interface. 16 , 17 , 18 , 22 , 23 , 24 Interference at any stage of this pathway can potentially compromise placenta formation and cause miscarriage. For example, recurrent miscarriage is associated with loss of BM-MSC during the implantation window with the level of depletion correlating to the number of previous losses.…”
Section: Miscarriage Syndrome: a Common Pathological Pathwaymentioning
confidence: 99%
“…Notably, other immune cells also play important roles in maintaining the integrity of the maternal-fetal interface in early gestation, including dentritic cells, activated regulatory T cells, and anti-inflammatory (M2) macrophages. 16 , 17 , 18 , 22 , 23 , 24 , 28 , 29 , 30 …”
Section: Miscarriage Syndrome: a Common Pathological Pathwaymentioning
confidence: 99%
“…For instance, the chemokine C-X-C motif chemokine ligand 12 (CXCL12) has been found to play a major role in recruiting BM-derived progenitor cells into the uterus during pregnancy in mice, via its interaction with the C-X-C chemokine receptor type 4 (CXCR4) receptor on these cells. This recruitment, in turn, facilitates the formation of the characteristic decidual structures of the pregnant endometrium, which is essential for ensuring successful implantation of the fetus in the uterus [ 100 ]. Even under non-pregnant conditions, these BM-derived progenitor cells are still able to traffic into the uterus and differentiate into cells similar to that of endogenous uterine cells, such as the endometrium, in a BM replacement study [ 101 ].…”
Section: Utero-cardiac Axis Involves a 3-way Relationship Between Hea...mentioning
confidence: 99%